Training the shoulder complex in baseball pitchers: A sport-specific approach - Jeran, J. J.; Chetlin, R. D. (Strength and Conditioning Journal, 2005)
The purpose of this paper is to identify exercise performance-related factors which may contribute to shoulder pain and dysfunction and to describe appropriate training strategies for promoting shoulder stability and enhanced function. The intent is not to help the reader diagnose and treat injuries or to prescribe therapeutic interventions. Strength and conditioning professionals should encourage injured clients to consult a physician, physical therapist, or other appropriate health care professional before starting a conditioning program.